2017
DOI: 10.1016/j.atherosclerosissup.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A nutraceutical approach (Armolipid Plus) to reduce total and LDL cholesterol in individuals with mild to moderate dyslipidemia: Review of the clinical evidence

Abstract: Compelling evidence supports the effectiveness of the reduction of total and LDL cholesterol (TC and LDL-C) in primarily preventing cardiovascular events, within the framework of life-long prevention programs mainly consisting in lifestyle changes. Pharmacological treatment should be introduced when lifestyle changes, including use of nutraceuticals, have failed. ESC/EAS guidelines list a number of nutraceutical compounds and functional foods which have been individually studied in randomized, controlled clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
66
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 62 publications
10
66
0
6
Order By: Relevance
“…Monacolin K has an affinity of about 2000 times compared to the endogenous substrate and can modulate the lipid profile by reducing TC and LDLC [19]. A recent study carried out in patients intolerant to statins reported that RYR was as effective as pravastatin in inducing a dose-dependent decrease of LDLC levels, with a superior safety and tolerability profile [20].…”
Section: Discussionmentioning
confidence: 99%
“…Monacolin K has an affinity of about 2000 times compared to the endogenous substrate and can modulate the lipid profile by reducing TC and LDLC [19]. A recent study carried out in patients intolerant to statins reported that RYR was as effective as pravastatin in inducing a dose-dependent decrease of LDLC levels, with a superior safety and tolerability profile [20].…”
Section: Discussionmentioning
confidence: 99%
“…Besides extensive animal studies in rabbits (Luo, He, Jin, Zhou, & Yang, ), rats (Jia et al, ; Jin, He, Zhou, & Yang, ), and mice (Chueh & Lin, ), the lipid‐lowering efficacy of berberine has been evaluated by randomized, placebo‐controlled clinical trials in patients with hypercholesterolemia who cannot tolerate statins; in patients with mild to moderate mixed hyperlipidemia, with and without concomitant type 2 diabetes mellitus; and in patients with hyperlipidemia cirrhosis or hepatitis B and C. Mean reductions in TG and LDL‐C levels have been reported at approximately 13–30% and 20–25%, respectively (Barrios et al, ).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Red yeast rice and policosanol target the HMG‐CoA reductase enzyme, but in different ways, monacolin K, the active ingredient of red yeast rice, competitively inhibits HMG‐CoA reductase activity; whereas policosanol decreases HMG‐CoA reductase synthesis. Berberine has broad effects on the lipid profile via the LDL liver uptake and TG synthesis (Barrios et al, ). Large interindividual inconsistency has been reported in the plasma LDL‐C response to Armolipid Plus supplementation and attributed to three polymorphisms in the 30 UTR region of LDLR, c.*773A > G, c.*52G > A, and c.*504G > A; and two at the 50 UTR region of PCSK9, c.−2,063A > G and c.−3,383C > G (De Castro‐Orós et al, ).…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…For these reasons, a nutraceutical treatment with substances characterized by complementary lipidlowering properties was started in 2003, including red yeast rice, policosanol, and berberine combined with folic acid, astaxanthin, and coenzyme Q10 (Armolipid Plus® 1 cp/die). 10 The patient came to our attention in December 2015. At the physical examination: body weight 5 68 kg, height 5 158 cm, BMI5 27.3 kg/m 2 , ambulatory blood pressure 5 120/84 mm Hg.…”
Section: Ase Re Portmentioning
confidence: 98%
“…Unfortunately, muscle symptoms and CK elevation reappeared. For these reasons, a nutraceutical treatment with substances characterized by complementary lipid‐lowering properties was started in 2003, including red yeast rice, policosanol, and berberine combined with folic acid, astaxanthin, and coenzyme Q10 (Armolipid Plus® 1 cp/die) …”
Section: Case Reportmentioning
confidence: 99%